Body of lies - DiCaprio, Leonardo; DeLine, Donald; Scott, Ridley; Warner Bross Pictures; De Line Pictures; Scott Free Productions ([Burbank, CA] : Warner Bross Pictures, 2009)
As CIA operative Roger Ferris makes plans to infiltrate a terrorist network operating in Jordan, he starts to question the motives of the Jordanian man helping him on the ground and a CIA colleague back in the United States
Title from title screen
Based on the novel by David Ignatius
Director of photography, Alexander Witt ; editor, Pietro Scalia ; music, Marc Streitenfeld
Cast: Leonardo DiCaprio, Russell Crowe, Mark Strong, Golshifteh Farahani, Oscar Isaac
In English or Thai with optional English, Bahasa Indonesia, Thai, Korean or Chinese subtitles
Keywords: Ignatius, David, -- 1950- -- Film and video adaptations; Spies -- United States -- Drama; Terrorists -- Jordan -- Drama; Infiltration (Military science) -- Drama